Potret Pribadi Hari Esok: Kajian Perspektif Carl Rogers pada Siswa Sekolah Menengah - Fitri Yulianti; Astri Rachmahyani; M. Fiqri Syahril (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2026)
Adolescence is an important phase in personality formation and individuals’ orientation toward the future. From the perspective of humanistic psychology, Carl Rogers introduced the concept of the person of tomorrow as an individual who holds a positive view of the self and the future and is capable of functioning optimally. This study aims to describe the profile of the person of tomorrow among senior high school/vocational school students based on Carl Rogers’ perspective. The study employed a descriptive quantitative approach using a survey method involving 241 students from SMA/SMK in Bandung Regency, selected through purposive sampling. The instrument used was the Person of Tomorrow Scale consisting of 33 Likert-type items (1–5) covering seven indicators. Instrument validity testing using the Rasch model showed that all items met the criteria of Outfit MNSQ (0.5–1.5), ZSTD (-3.3 to 2.9), and Point Measure Correlation (0.34–0.53). The instrument reliability demonstrated a Cronbach’s Alpha of 0.91 (excellent), person reliability of 0.85 (good), and item reliability of 0.98 (excellent). Data analysis was conducted using descriptive statistics through mean scores, standard deviation, and empirical norm-based categorization (M ± 1SD). The results indicated that the profile of the person of tomorrow was at a moderate level (72%), with 15% in the high category and 13% in the low category. All indicators were also at a moderate level, indicating that the characteristics of the person of tomorrow have begun to develop among students but have not yet reached an optimal condition and still require further strengthening. This study provides empirical contributions to the humanistic concept of Rogers in the Indonesian student context and serves as a basis for developing counseling and guidance services focused on strengthening the characteristics of the person of tomorrow. ____________________________________________________________Masa remaja merupakan fase penting pembentukan kepribadian dan orientasi individu terhadap masa depan. Dalam perspektif psikologi humanistik, Carl Rogers mengemukakan konsep the person of tomorrow sebagai gambaran individu yang memiliki pandangan positif terhadap diri dan masa depan serta kemampuan berfungsi secara optimal. Penelitian ini bertujuan untuk mendeskripsikan profil the person of tomorrow pada peserta didik SMA/SMK berdasarkan perspektif Carl Rogers. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan metode survei terhadap 241 siswa SMA/SMK di Kabupaten Bandung yang dipilih melalui teknik purposive sampling. Instrumen yang digunakan adalah The Person of Tomorrow Scale yang terdiri dari 33 item skala Likert (1–5) dengan tujuh indikator. Uji validitas instrumen menggunakan model Rasch menunjukkan seluruh item memenuhi kriteria Outfit MNSQ (0,5–1,5), ZSTD (-3,3 hingga 2,9), serta Point Measure Correlation (0,34–0,53). Reliabilitas[FY1]  instrumen menunjukkan nilai Cronbach’s Alpha sebesar 0,91 (sangat baik), reliabilitas person 0,85 (baik), dan reliabilitas item 0,98 (sangat baik). Analisis data dilakukan menggunakan statistik deskriptif melalui perhitungan skor rata-rata, standar deviasi, serta kategorisasi berbasis norma empiris (M ± 1SD). Hasil penelitian menunjukkan bahwa profil the person of tomorrow berada pada kategori sedang (72%), kategori tinggi (15%), dan kategori rendah (13%). Seluruh indikator juga berada pada kategori sedang, yang menunjukkan bahwa karakteristik pribadi hari esok telah mulai berkembang pada peserta didik, namun belum mencapai kondisi yang optimal dan masih memerlukan penguatan lebih lanjut. Penelitian ini memberikan kontribusi empiris dalam mengkaji konsep humanistik Rogers pada konteks peserta didik Indonesia serta menjadi dasar pengembangan layanan bimbingan dan konseling berbasis penguatan karakteristik the person of tomorrow.